THERAPEUTIC PROFILING OF NANO ENCAPSULATED DIOSGENIN VIA ATTENUATING HORMONAL STATUS, CELL PROLIFERATION, INFLAMMATORY RESPONSES, AND APOPTOSIS IN AN ANIMAL MODEL OF MAMMARY ONCOGENESIS - VENGAIMARAN, MANOBHARATHI; DHAMODHARAN, KALAIYARASI; SANKARAN, MIRUNALINI (International Journal of Applied Pharmaceutics, 2021)
Objective: The central motive of this study is to explore the therapeutic impact of Diosgenin encapsulated Chitosan nanoparticles (DG@CS-NP) on mammary carcinogenesis in female Sprague Dawley rats via modulating hormonal status, cell proliferation, inflammatory responses, and Apoptosis. Methods: 7,12-dimethylbenz(a)anthracene (DMBA) was administered subcutaneously near the mammary gland (25 mg/kg b. wt) to provoke mammary tumor in female Sprague Dawley rats. Following the progress of a tumor, DMBA-induced tumor-bearing rats were medicated orally with 5 mg/kg b. wt of DG@CS-NP. Consequently, the expression of ER, PR, PCNA, Cyclin D1, NF-κB, TNF-α, Bcl-2, Caspases-3, and p53 in experimental rats were revealed via architectural immunohistochemistry. Further, Diosgenin interactions with these proteins were evidently confirmed by molecular docking analysis. Results: As a result, we noticed diminished levels of ER, PR, PCNA, Cyclin D1, NF-κB, TNF-α, and Bcl-2 expressions in DG@CS-NP medicated rats as well as with elevated levels of Caspases-3 and p53 expressions. In DMBA rats, the expressions were vice versa. Additionally, molecular docking analyses support these outcomes by highlighting the strong interaction between Diosgenin and breast cancer targets. Conclusion: These reports prove that DG@CS-NP imposes its therapeutic impact by hormonal adjustments, downregulating proteins involved in inflammation and cellular proliferation, and thereby promotes apoptosis by impeding apoptotic inhibitors.